Analysis of Toll-Like Receptors, iNOS and Cytokine Profiles in Patients with Pulmonary Tuberculosis during Anti-Tuberculosis Treatment - Cardoso de Oliveira, Larissa Ragozo [UNESP]; Peresi, Eliana [UNESP]; Golim, Marjorie de Assis [UNESP]; Gatto, Mariana [UNESP]; Araujo Junior, Joao Pessoa [UNESP]; Pellison Nunes da Costa, Erika Alessandra [UNESP]; Ayres, Jairo Aparecido [UNESP]; Parise Fortes, Maria Rita [UNESP]; Calvi, Sueli Aparecida [UNESP] (Public Library Science, 2014)
Toll-like receptors (TLRs) play an important role in mycobacterial infection, although little is known about the roles of these receptors, cytokines and nitric oxide during anti-tuberculosis treatment. Our objective was to evaluate the mRNA and cell surface expression of TLR2 and TLR4; inducible nitric oxide synthase (iNOS) expression; and cytokine Th1, Th2 and Th17 profiles in pulmonary tuberculosis patients at different time points of anti-tuberculosis treatment. Peripheral blood mononuclear cells (PBMCs) were obtained from PPD+ healthy controls and from patients receiving anti-tuberculosis treatment. Gene expression quantification was performed by qPCR, cell surface expression was assessed using flow cytometry, and cytokine quantification was conducted using the CBA technique. The treated patients presented higher gene expression and higher numbers of receptors on the cell surface of lymphocytes and monocytes than did control individuals. IL-12 and IFN-gamma levels increased after the start of treatment, whereas TNF-alpha levels were reduced. TGF-beta presented the highest levels during treatment. IL-10 and IL-17 expression and production tended to increase during treatment. iNOS gene expression was reduced throughout treatment in patients. Our results suggest that anti-tuberculosis treatment modulates the immune response, inducing an increase in the expression of TLRs and pro-and anti-inflammatory cytokines to combat bacteria and reduce the inflammatory process.